John Adams [compact disc, unabridged] - McCullough, David G. (Simon & Schuster Audio ; Home Box Office (HBO), 2008)
Biography of John Adams portraying him as a brilliant, fiercely independent Yankee patriot who spared nothing in his zeal for the American Revolution and then rose to become the second president of the United States.